Einige kritische Überlegungen zur geistigen Situation der Gegenwart - Harald Schöndorf (Jesuit University Ignatianum in Krakow, 2009)
The article aims at presenting a few extremely important phenomena of the present time, which largely determine the spiritual condition of our time. The author mentions here faith in science, whose research results, often expressed in figures, are often taken uncritically. Another characteristic of current situation is admiration for technology, and on account of the damage it has done to the environment, it is being replaced with admiration for the environment, which - as some people claim - shall be saved at all costs. Here, the battle against climate warming becomes a substitute for religion, which is showed by the intensity of ecologists' activities and the dogmatic obeying of the arguments which perceive man as the only source of climatic changes. The fear of a climatic catastrophe becomes here an essential motive for limiting energy imported. Social structure, with families which today usually have only one child results in the increasing process of individualization, non conducive to building social bonds. Another growing phenomenon - professionalization often leads to the financial compensation for any social activity, which is becoming a great strain for the Budget. And in the field of science we deal with its extreme dependence on the financial resources. Their significant depletion forces scientists to look for them in industry, which in turn forces them to demonstrate the usefulness of their research. Philosophy, as a science, has not managed to develop the non-antinomic thinking about freedom and the world of objects. This field of science does not take economic issues into consideration in its reflection, and even if it does, it is only in the context of ethical questions.